The waste of time – how a lower opportunity cost could increase households’ recycling effort : an empirical analysis of the effect of curbsiderecycling on waste sorting efforts in Swedishmunicipalities - Hoff Rudhult, Linda (SLU/Dept. of Economics, 2017)
Introduction of residential curbside recycling programs are assumed to have a positive effect on households’ waste sorting effort since it facilitates recycling in the context of daily life and provides a lower behavioural cost in terms of time, effort and storage cost compared to drop-off recycling. In Sweden, three different systems for curbside collection are used for waste sorting; four-compartment bins, different coloured bags, and bags and containers. The purpose of this study is to empirically evaluate curbside recycling program and to estimate the change in waste sorting effort in Swedish municipalities when residents living in single-family houses makes a transition from drop-off recycling to curbside recycling of packaging waste and newspaper. Econometric regression models are applied on unbalanced panel data for 264 municipalities during the time period 2007-2015. Fixed-effect regression model are used with additional control for region-specific characteristics and for waste management policies used. The results indicate a significant but weak support for a better waste sorting behaviour among municipalities providing curbside recycling with different coloured bags.